Hatchery design appropriate for shrimp production in Basrah, Iraq - Ghazi, Abdul-Hussein H.; Al–Noor, Sajed S.; Ali, Malik H. (Iraqi Journal of Aquaculture, 2021)
The present study suggested a medium hatchery design for production of about 8,000,000 larvae / year in Basrah region. All the requirements, such as, water treatment shrimp culture ponds and all tools and equipment are given and discussed